Corpora and Students' Autonomy in Scientific and Technical Translation training - Clara Inés López-Rodríguez; María Isabel Tercedor-Sánchez (JoSTrans: The Journal of Specialised Translation)
The use of corpora in the translation classroom has been explored by several researchers (Bowker 1998, 2000; Faber et al 2001; Zanettin, Bernardini & Stewart 2003). The aims of this paper are to explore the applications of corpora in the teaching of scientific and technical translation at university level, and to design activities that increase learner autonomy while developing translation strategies and evaluation skills. These activities include the analysis of three types of corpora (DIY corpora, learner corpora, and a quality corpus), the introduction of tags for didactic purposes, and the generation of lemmatised wordlists and concordances. We also explore how corpora contribute to the acquisition of knowledge of the subject field and its conventions, and to the production of adequate texts in the target language.